No evidence for intermediate-mass black holes in globular clusters: Strong constraints from the JVLA - Strader, J.; Chomiuk, L.; Maccarone, T.; Miller-Jones, James; Seth, A.; Heinke, C; Sivakoff, G. (Institute of Physics Publishing Ltd., 2012)
With a goal of searching for accreting intermediate-mass black holes (IMBHs), we report the results of ultra-deep Jansky Very Large Array radio continuum observations of the cores of three Galactic globular clusters: M15, M19, and M22. We reach rms noise levels of 1.5–2.1 μJy beam−1 at an average frequency of 6 GHz. No sources are observed at the center of any of the clusters. For a conservative set of assumptions about the properties of the accretion, we set 3σ upper limits on IMBHs from 360 to 980 M☉ . These limits are among the most stringent obtained for any globular cluster. They add to a growing body of work that suggests either (1) IMBHs >~ 1000 M☉ are rare in globular clusters or (2) when present, IMBHs accrete in an extraordinarily inefficient manner.